A Sudden Onset of Severe Thrombocytopenia While Using Evolocumab. (26th March 2020) - Inoue, Ikuo; Takenaka, Yasuhiro; Kin, Yoshitora; Yamazaki, Satoshi; Ikegami, Yuichi; Saito, Daigo; Shimada, Akira
Abstract : A 72-year-old man with a 10-year history of coronary heart disease started evolocumab treatment once a month after developing excess myalgia due to therapy with a 3-hydroxy-methylglutaryl CoA reductase inhibitor. No side effects such as myalgia symptoms had been reported during the first 14 months of evolocumab treatment; however, he suddenly presented with acute severe thrombocytopenia following the 14th treatment. His platelet count continued to decrease to a nadir of 1, 000/ μ L. His platelet-associated immunoglobulin G level had elevated to 790 ng/10 7  cells. He started receiving a combination of steroid therapy, high-dose immunoglobulin therapy, and platelet transfusions, but the first-line therapy was ineffective. He was subsequently treated with a thrombopoietin receptor agonist, and his platelet count recovered to 250, 000/ μ L.